2019
DOI: 10.1101/684357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transfer learning enables prediction ofCYP2D6haplotype function

Abstract: A major limitation of phenotype prediction in genetics is the ability to model the complexities of genetic variation when sample sizes are small. This is especially true in pharmacogenetics, ahighly translational yet data-limited subfield of genetics. Drug metabolism is a critical facet of pharmacogenetics and can have consequences for drug safety and efficacy. CYP2D6 is an 1 important enzyme, metabolizing more than 25% of clinically used drugs. It is highly polymorphic which leads to a heterogeneous response … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…An alternative to defining individual haplotypes and/or driving mutations, is to take a top down approach, in which regions of the gene or genes themselves are deemed essential, and any deleterious variant within essential components can be assigned an inferred phenotype. Recent work on the development of data-driven PGx phenotyping methods indicates that given enough data, it might be possible to move away from variant level rule-based systems and towards data-driven machine-learning models capable of robustly handling unobserved genetic variation 13,24,25 . The challenges posed by rare variation is likely to be a consistent issue for the current PGx system and will likely grow over time as genotyping gives way to genome sequencing and more populations are studied in detail revealing more rare and/or private mutations harbored by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to defining individual haplotypes and/or driving mutations, is to take a top down approach, in which regions of the gene or genes themselves are deemed essential, and any deleterious variant within essential components can be assigned an inferred phenotype. Recent work on the development of data-driven PGx phenotyping methods indicates that given enough data, it might be possible to move away from variant level rule-based systems and towards data-driven machine-learning models capable of robustly handling unobserved genetic variation 13,24,25 . The challenges posed by rare variation is likely to be a consistent issue for the current PGx system and will likely grow over time as genotyping gives way to genome sequencing and more populations are studied in detail revealing more rare and/or private mutations harbored by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…FATHMM was utilized to predict functional consequences of non-coding variants, it integrates functional annotations from ENCODE and calculates a score (0–1). Scores >0.5 are indicative of deleterious variation (McInnes et al, 2019; Zhou et al, 2018), and although non-coding variants may not have a direct impact on a protein the overall regulation may render faulty. These tools have been utilized in PGx research (Devarajan et al, 2019), and we have reported their use to filter variants with potential effects on atorvastatin pharmacokinetics with acceptable results.…”
Section: Methodsmentioning
confidence: 99%
“…This high-throughput functional screening approach has been successfully applied to NUDT15 and could be conceivably applied to CYP2D6 [111]. Analysis of large datasets is another approach to assign functional effects to these undetermined haplotypes, and is being increasingly carried out to interrogate CYP2D6 [112,113]. One example is the use of sequence data and phenotypic data from >450,000 UK biobank participants [112].…”
Section: Novel Approaches To Cyp2d6 Phenotypingmentioning
confidence: 99%
“…Analysis of large datasets is another approach to assign functional effects to these undetermined haplotypes, and is being increasingly carried out to interrogate CYP2D6 [112,113]. One example is the use of sequence data and phenotypic data from >450,000 UK biobank participants [112]. Analysis of these data has been used to elucidate haplotypes, but it was unable to capture structural variations.…”
Section: Novel Approaches To Cyp2d6 Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation